Educational and Moral Views of Abdurakhman Jami and Pedagogical Views of Alisher Navoi - Eshkeldiyeva , Sabina; Eshmominova , Dilfuza (Journal of Pedagogical and Philological Research, 2026)
This topic highlights the views of Abdurakhman Jami and Alisher Navoi on education, upbringing, morality, and human perfection. In his works, Jami emphasizes that the main path leading a person to spiritual maturity is science, manners, and ethics. According to him, virtues such as patience, honesty, humility, and hard work play an important role in raising a perfect human being. Alisher Navoi, in his pedagogical thoughts, shows the importance of education in the development of society and the necessity of raising the younger generation to be knowledgeable and well-mannered. In Navoi's works, ideas of respect for the teacher, love for science, justice, and humanism occupy a central place. Through this topic, the views of the two great thinkers on upbringing, their pedagogical legacy, and their significance in today's education system are revealed.